2007
DOI: 10.1042/cs20060365
|View full text |Cite
|
Sign up to set email alerts
|

Acute elevation of plasma non-esterified fatty acids increases pulse wave velocity and induces peripheral vasodilation in humans in vivo

Abstract: Plasma NEFA (non-esterified fatty acid) concentrations are elevated in patients with obesity. In the present study we first aimed to provide an integral haemodynamic profile of elevated plasma NEFAs by the simultaneous assessment of blood pressure, pulse wave velocity, FBF (forearm blood flow) and sympathetic nervous system activity during acute elevation of NEFAs. Secondly, we hypothesized that NEFA-induced vasodilation is mediated by adenosine receptor stimulation. In a randomized cross-over trial in healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…While FFAs and triglycerides were measured at similar times, we did not undertake formal protocols to prevent lipolysis ex vivo, and this may have affected our results. The results from this study suggest that the acute effects of increased circulating triglycerides may have very different effects compared with the chronic setting, such as potential vasoconstriction and increased BP with longer exposure to raised lipids (26,29). However, this is only speculation, since the current study investigated the acute but not chronic response to IFE.…”
Section: Discussioncontrasting
confidence: 48%
“…While FFAs and triglycerides were measured at similar times, we did not undertake formal protocols to prevent lipolysis ex vivo, and this may have affected our results. The results from this study suggest that the acute effects of increased circulating triglycerides may have very different effects compared with the chronic setting, such as potential vasoconstriction and increased BP with longer exposure to raised lipids (26,29). However, this is only speculation, since the current study investigated the acute but not chronic response to IFE.…”
Section: Discussioncontrasting
confidence: 48%
“…Most studies are in agreement that NEFAs promote insulin resistance and impair endothelium-dependent vasodilation [22][23][24]; however, the endothelial dysfunction documented in these investigations is typically associated with a paradoxical increase in basal limb blood flow. Although few studies have examined the underlying mechanisms of increased basal limb blood flow from elevated NEFA levels [25][26][27], possible explanations include insulin-induced NO release or vasodilating prostaglandin production [26].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Intralipid on vasculature is also controversial 3739 . Intralipid has been shown to promote peripheral vasodilation in humans 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Intralipid has been shown to promote peripheral vasodilation in humans 37 . Osanai et al, however showed that Intralipid impaired postischemic endothelium-dependent vasodilatation in the canine iliac artery 39 .…”
Section: Discussionmentioning
confidence: 99%